2021
DOI: 10.1186/s43168-021-00054-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and C-reactive protein/albumin ratio as predictors of COVID-19 severity and mortality

Abstract: Background Coronavirus disease 2019 (COVID-19) was announced in early December 2019. The pandemic situation is declared. This study aimed to evaluate the role of biomarkers in estimating the severity and predicting the prognosis of COVID-19. Results A total of 116 confirmed patients were included in this study. The patients were evaluated clinically. The disease severity was assessed. The measured and calculated laboratory tests were done. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
45
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 30 publications
(28 reference statements)
11
45
2
1
Order By: Relevance
“…Hence, based on our findings CRP/Albumin ratio can be used as a predictor of disease severity, but not mortality in COVID-19 patients. Our study significantly adds to the emerging scant literature on CRP/Alb ratio and its utility in patients with SARS-CoV-2 infection, to our knowledge there only few studies and their results do not necessarily corroborate with our findings [21,22,23]. This could be secondary to varying methods in differentiating disease severity, ethnicity, population differences and most importantly small sample sizes.…”
Section: Discussioncontrasting
confidence: 70%
“…Hence, based on our findings CRP/Albumin ratio can be used as a predictor of disease severity, but not mortality in COVID-19 patients. Our study significantly adds to the emerging scant literature on CRP/Alb ratio and its utility in patients with SARS-CoV-2 infection, to our knowledge there only few studies and their results do not necessarily corroborate with our findings [21,22,23]. This could be secondary to varying methods in differentiating disease severity, ethnicity, population differences and most importantly small sample sizes.…”
Section: Discussioncontrasting
confidence: 70%
“…Besides, we found that age, gender, comorbidities, or the presence of fever on presentation did not show a significant effect on the tested outcomes. COVID-19 induces generalized inflammation, which can cause serious multiple organ damage and complicate the infection [ 26 , 27 ]. Therefore, assessment of the laboratory parameters should be adequately done to avoid these complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, because high IL-6 levels and low lymphocyte counts have been connected to the severity and in-hospital mortality of COVID-19, in a study by Yang and colleagues, the IL-6/lymphocyte ratio (IL-6/L, reversed) was described as a novel biomarker to conduct risk stratification in COVID-19 patients [7]. Other studies have found that having a high IL-6/L is an independent risk factor for disease progression and a poor prognosis [29, 30]. The decrease in lymphocyte numbers caused by IL-6-mediated inhibition of T cell activation explained the high in COVID-19 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, El-Shabrawy and colleagues have found that the CRP/alb was a predictive factor of COVID-19 mortality. 28…”
Section: Discussionmentioning
confidence: 99%